2019
DOI: 10.1016/j.sjbs.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-resistant Staphylococcus epidermidis isolated from patients and healthy students comparing with antibiotic-resistant bacteria isolated from pasteurized milk

Abstract: Antibiotic-resistant Staphylococci are a global issue affecting humans, animals, and numerous natural environments. Antibiotic-resistant Staphylococcus epidermidis is an opportunistic pathogen frequently isolated from patients and healthy individuals. This study aimed to examine the antibiotic resistance of S. epidermidis isolated from patients, healthy students and compare the results with antibiotic-resistant bacteria isolated from pasteurized milk. Clinical strain isolation was performed in several hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 28 publications
5
14
1
Order By: Relevance
“…Staphylococcus aureus recorded the increasing trend of resistance to tetracycline, erythromycin and clindamycin which is consistent to other researchers' reports (Ashkenazi et al, 2003). A study conducted by Eladli et al (2019) also revealed the antibiotic resistance of fosfomycin and erythromycin onto S. epidermidis. As the subject of the study included patient and healthy people, the study concluded that multi-resistant S. epidermidis strains are widespread among them.…”
Section: Introductionsupporting
confidence: 89%
“…Staphylococcus aureus recorded the increasing trend of resistance to tetracycline, erythromycin and clindamycin which is consistent to other researchers' reports (Ashkenazi et al, 2003). A study conducted by Eladli et al (2019) also revealed the antibiotic resistance of fosfomycin and erythromycin onto S. epidermidis. As the subject of the study included patient and healthy people, the study concluded that multi-resistant S. epidermidis strains are widespread among them.…”
Section: Introductionsupporting
confidence: 89%
“…In case of MRSA infections, antibiotic monotherapy (vancomycin, teicoplanin, telavancin, daptomycin, ceftaroline, linezolid) and antibiotic combination therapy (vancomycin and beta-lactams, ceftaroline and daptomycin) have limitations with respect to tolerance, side effects, costs, development of resistance and cross-resistance ( Choo and Chambers, 2016 ). Same limitations arise in the treatment of the infections caused by resistant S. epidermidis , common in broken-skinned, immunocompromised and implanted patients ( Eladli et al, 2019 , Otto, 2009 ). Therefore, combinations of antibiotics with natural products, exhibiting synergistic interactions, represent a promising strategy to achieve increased efficacy and reduced side effects ( Zhou et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the prevalence of resistance against tetracycline (51%), erythromycin (41.20%), oxacillin (97.70%), cephazolin (58.30), and norfloxacin (51.90%) was entirely high [18]. Eladli et al [19] reported that the prevalence of antibiotic resistance of the S. epidermidis strains against amoxicillin-clavulanic acid, ciprofloxacin, clindamycin, erythromycin, gentamicin, levofloxacin, mupirocin, oxacillin, rifampin, tetracycline, and trimethoprim-sulfamethoxazole antibiotics was 100%, 100%, 37%, 0%, 33%, 16%, 0%, 80%, 0%, 80%, and 0%, respectively. Ma et al [20] reported that the prevalence of antibiotic resistance of the coagulase-negative staphylococci strains against penicillin, oxacillin, erythromycin, tetracycline, clindamycin, ciprofloxacin, trimethoprim-sulfamethoxazole, chloramphenicol, ceftizoxime, gentamicin, rifampin, teicoplanin, and vancomycin antibiotics were 94.20%, 79.10%, 89.50%, 59.50%, 53.70%, 52.80%, 58.50%, 39.10%, 26.70%, 29.50%, 18.40%, 2.30, and 0%, respectively.…”
Section: Discussionmentioning
confidence: 99%